Phylogeograpy of Aphanicercella cassida (Plecoptera : Notonemourida) : cryptic speciation? - Van Alphen-Stahl, Jonathan (Department of Biological Sciences, 2017)
Stoneflies (Plecoptera) in South Africa are limited to cool pristine mountain streams. This provides them with very limited habitat in which to survive. The species of stonefly studied in this project (Aphanicercella cassida) has a very wide distribution unlike most other species which have a limited range. Of particular interest is a population in Mpumalanga (north of South Africa) which is very disjunct from the other populations of A. cassida found widely in the southwestern Cape. Despite this large geographic distance the insects appear to be morphologically identical to one another. It is believed that there is limited or no gene flow between the northern and southern populations as stoneflies are poor fliers. Molecular analysis of the cytochrome oxidase I gene in the mitochondrial DNA was analysed to see if any genetic differentiation was occurring inspite of the morphological homogeneity. A 557 base pair region was compared across three populations of A. cassida one in Mpumalanga and two in the southwestern Cape. Two congeneric species, A. bullata and A. scutata, were used as outgroups. The findings of this study were quite dramatic. The northern population is extremely different from the southern populations at the molecular level. There is more variation between the two populations of A. cassida than between the two outgroup species and the split between the two disjunct populations displays evidence of an ancient vicariance event. This finding definitely warrants further investigation into whether the population of A. cassida in Mpumalanga is a cryptic species. More sampling has to be done within the studied populations and more populations should be added to the analysis before any definite decision can be made regarding this fascinating emergence of possible cryptic species in South African stoneflies.